You are on page 1of 11

Chapter 2: Sequence

Example: Find the next term 1, 3, 5, 7, 9, ?


Example: 𝑢𝑢𝑛𝑛 = 𝑎𝑎1 𝑢𝑢𝑛𝑛−1 + 𝑎𝑎2 𝑢𝑢𝑛𝑛−2 by knowing given number sequence: 1, 3, 4, 7, 11, 18,
Example: Prove for sequence relationship expression.

Instigation: Tower of Hanoi


The minimal number of moves required to solve a Tower of Hanoi puzzle is 2n − 1, where n is the number of disks.
𝑢𝑢𝑛𝑛 = 2𝑛𝑛 − 1

2.1 Describing Sequences

A sequence is simply an ordered list of numbers.

𝑎𝑎0 , 𝑎𝑎1 , 𝑎𝑎2 , 𝑎𝑎3 , …

To refer to the entire sequence at once, we will write (an)n∈N or (an)n≥0,

The numbers in the subscripts are called indices (the plural of index).

The sequence (an)n≥0 is a function with domain N where an is the image of the natural number n.

Closed formula:

A closed formula for a sequence (an)n∈N is a formula for an using a fixed finite number of operations on n.
This is what you normally think of as a formula in n, just as if you were defining a function in terms of n
(because that is exactly what you are doing).

Example: 𝑎𝑎𝑛𝑛 = 2𝑛𝑛 − 1

Example: 1, 3, 5, 7, 9,…, we have (𝑎𝑎𝑛𝑛 )𝑛𝑛∈ℕ = 2𝑛𝑛 + 1

Recursive definition:
A recursive definition (sometimes called an inductive definition) for a sequence (an)n∈N consists of a
recurrence relation : an equation relating a term of the sequence to previous terms (terms with smaller index)
and an initial condition: a list of a few terms of the sequence (one less than the number of terms in the recurrence
relation).

Example: 1, 3, 5, 7, 9,…, we have 𝑎𝑎𝑛𝑛 = 𝑎𝑎𝑛𝑛−1 + 2, 𝑎𝑎0 = 1


𝑇𝑇𝑛𝑛 − 𝑇𝑇𝑛𝑛−1 = 𝑛𝑛

Partial Sum

Some sequences naturally arise as the sum of terms of another sequence.

Example:

(𝑎𝑎𝑛𝑛 )𝑛𝑛≥ 0 : 3,5,6,10,9,0,12,....

(𝑏𝑏𝑛𝑛 )𝑛𝑛≥ 0 : 3,8,14,24,33,33,45,....

The partial sum of a sequence:


The partial product of a sequence:

2.2 Arithmetic and geometric sequences

Sums of Arithmetic and Geometric Sequences


Summing Arithmetic Sequences: Reverse and Add

Reverse and add

Example: Use partial sums to find a closed formula for (an)n≥0 which starts
2,3,7,14,24,37,......
𝑎𝑎𝑛𝑛 = 𝑎𝑎𝑛𝑛−1 + 𝑏𝑏𝑛𝑛 , 𝑛𝑛 ≥ 1, 𝑎𝑎0 = 2
𝑏𝑏𝑛𝑛 = 1 + 3(𝑛𝑛 − 1)
𝑎𝑎𝑛𝑛 = 𝑎𝑎𝑛𝑛−1 + 1 + 3(𝑛𝑛 − 1)
On the other hand,
𝑎𝑎1 = 𝑎𝑎0 + 1 + 3(1 − 1)
𝑎𝑎2 = 𝑎𝑎1 + 1 + 3(2 − 1)
𝑎𝑎3 = 𝑎𝑎2 + 1 + 3(2 − 1)

𝑎𝑎𝑛𝑛 = 𝑎𝑎𝑛𝑛−1 + 1 + 3(𝑛𝑛 − 1)

3𝑛𝑛(𝑛𝑛 − 1)
𝑎𝑎𝑛𝑛 = 𝑎𝑎0 + 𝑛𝑛 +
2

Summing Geometric Sequences: Multiply, Shift and Subtract

1 − 𝑟𝑟 𝑛𝑛+1
𝑆𝑆 = 𝑎𝑎0 + 𝑎𝑎1 + 𝑎𝑎2 + ⋯ + 𝑎𝑎𝑛𝑛 = 𝑎𝑎0
1 − 𝑟𝑟

Example: 0.464646…
𝑎𝑎0 = 0.46
𝑎𝑎1 = 0.01𝑎𝑎0 = 0.0046
𝑎𝑎2 = 0.01𝑎𝑎1 = 0.000046
1 − 0.01𝑛𝑛+1 0.46 46
𝑆𝑆 = lim 𝑎𝑎0 + 𝑎𝑎1 + 𝑎𝑎2 + ⋯ + 𝑎𝑎𝑛𝑛 = lim 0.46 = =
𝑛𝑛→∞ 𝑛𝑛→∞ 1 − 0.01 0.99 99
Example:

(5+2)*2=14, (5+7)*2=24, (7+12)*2=38, (12+19)*2=62


𝑎𝑎1
𝑎𝑎2 = � + 5� ∗ 2 = 𝑎𝑎1 + 10
2
𝑎𝑎1 𝑎𝑎2
𝑎𝑎3 = � + � ∗ 2 = 𝑎𝑎1 + 𝑎𝑎2
2 2
𝑎𝑎2 𝑎𝑎3
𝑎𝑎4 = � + � ∗ 2 = 𝑎𝑎2 + 𝑎𝑎3
2 2

𝑎𝑎𝑛𝑛 = 𝑎𝑎𝑛𝑛−2 + 𝑎𝑎𝑛𝑛−1
Fibonacci number

2.3 Polynomial Fitting

Example: Given 1, 5, 14, 30, 55, 91....

First difference: 4, 9, 16, 25, 36,…

Second difference: 5, 7, 9, 11, 13, …

Third difference: 2, 2, 2, 2, 2, …

We call this sequence as sequence ∆3-constant. In general, we will say a sequence is a ∆k-
constant sequence if the kth differences are constant.

Example 2.3.1: Find the value of k if it is ∆k-constant sequence:

1. 2,3,7,14,24,37,....

First difference: 1, 4, 7, 10, 13,…

Second difference: 3, 3, 3, 3, 3, …

Thus, it is a ∆2-constant sequence.

2. 1,8,27,64,125,216,....

First difference: 7, 19, 37, 61, 91,…


Second difference: 12, 18, 24, 30, …

Third difference: 6, 6, 6, …

Thus, it is a ∆3-constant sequence.

3. 1,2,4,8,16,32,64,....

First difference: 1, 2, 4, 8, 16, 32, …

Second difference: 1, 2, 4, 8,16, …

Since at kth difference, the obtained difference returns the original sequence.

This sequence is not ∆k-constant sequence.

∆0-constant sequence: constant sequence, example: 3, 3, 3, 3, 3, …

∆1-constant sequence: arithmetic sequence, example: 3, 6, 9, 12, 15, …

𝑎𝑎𝑛𝑛 = 𝑎𝑎0 + 𝑛𝑛𝑛𝑛

∆2-constant sequence: is the sum of an arithmetic sequence, example: 2,3,7,14,24,37,....


𝑛𝑛(𝑛𝑛+1) 𝑛𝑛2 𝑛𝑛
Example: 𝑎𝑎𝑛𝑛 = = +
2 2 2

𝑎𝑎𝑛𝑛 = 𝑏𝑏𝑘𝑘 𝑛𝑛𝑘𝑘 + 𝑏𝑏𝑘𝑘−1 𝑛𝑛𝑘𝑘−1 + ⋯ + 𝑏𝑏1 𝑘𝑘 + 𝑏𝑏0 for ∆k-constant sequence

Example 2.3.2:

3,7,14,24,37,… with 𝑎𝑎1 = 3. Find the closed formula of this sequence.

Solution:

We have the first difference: 4, 7, 10, 13,…

And the second difference: 3, 3, 3, 3, …

Thus, this sequence is ∆2-constant sequence.


Assume that 𝑎𝑎𝑛𝑛 = 𝑏𝑏2 𝑛𝑛2 + 𝑏𝑏1 𝑛𝑛 + 𝑏𝑏0

We can get 𝑎𝑎0 = 2, thus 𝑎𝑎0 = 𝑏𝑏0 = 2

(We have 𝑎𝑎1 = 3. To find 𝑎𝑎0 , we need to find the difference between 𝑎𝑎1 and 𝑎𝑎0

And, for the second difference: 3, 3, 3, 3, …

for the first difference: 4, 7, 10, 13,…

From the first difference: we can get the previous term (before 4) is 1, because

1, 4, 7, 10, 13,…

Thus, 𝑎𝑎1 − 𝑎𝑎0 = 1 or 𝑎𝑎0 = 𝑎𝑎1 − 1 = 3 − 1 = 2)

And, 𝑎𝑎1 = 𝑏𝑏2 + 𝑏𝑏1 + 2 = 3

𝑎𝑎2 = 4𝑏𝑏2 + 2𝑏𝑏1 + 2 = 7

𝑏𝑏 + 𝑏𝑏2 = 1
Thus, � 1
2𝑏𝑏1 + 4𝑏𝑏2 = 5
5−2
We have 𝑏𝑏2 = = 1.5
2

And, 𝑏𝑏1 = 1 − 1.5 = −0.5

Therefore, 𝑎𝑎𝑛𝑛 = 1.5𝑛𝑛2 − 0.5𝑛𝑛 + 2

Example: 1,5,14,30,55,… with 𝑎𝑎1 = 1

We have first difference: 4, 9, 16, 25,…

Second difference: 5, 7, 9,…

Third difference: 2, 2,…

We can add the previous term as:

Second difference: 3, 5, 7, 9,…

First difference: 1, 4, 9, 16, 25

Thus, 𝑎𝑎1 − 𝑎𝑎0 = 1, 𝑎𝑎1 = 1 or 𝑎𝑎0 = 0


2.4 Solving Recurrence Relations

Telescoping refers to the phenomenon when many terms in a large sum cancel out - so the sum “telescopes.”

The Characteristic Root Technique

an − an−1 − 6an−2 =0.

𝑎𝑎𝑛𝑛 = 𝑟𝑟 𝑛𝑛

𝑟𝑟 𝑛𝑛 − 𝑟𝑟 𝑛𝑛−1 − 6𝑟𝑟 𝑛𝑛−2 =0

𝑟𝑟 𝑛𝑛−2 (𝑟𝑟 2 − 𝑟𝑟 − 6) = 0, thus 𝑟𝑟 = 0, 𝑟𝑟 = 3, 𝑟𝑟 = −2

if given 𝑎𝑎𝑛𝑛 is non-zero, 𝑎𝑎𝑛𝑛 = 3𝑛𝑛 or 𝑎𝑎𝑛𝑛 = (−2)𝑛𝑛

In general, 𝑎𝑎𝑛𝑛 = 𝑐𝑐1 3𝑛𝑛 + 𝑐𝑐2 (−2)𝑛𝑛 , 𝑐𝑐1 and 𝑐𝑐2 can be found via initial condition

These recurrence relations are called linear homogeneous recurrence relations with constant coef- ficients.
The “homogeneous” refers to the fact that there is no additional term in the recurrence relation other than a
multiple of aj terms.

We take a break, we will start back at 9:10am.


2.5 Induction
8 cents stamps, 5 cents stamps

P(n) is a statement.

P(1), P(2), P(3), P(4), . . . ,

𝑃𝑃(1): false, 𝑃𝑃(2): false, 𝑃𝑃(3): false, 𝑃𝑃(4): false, 𝑃𝑃(5): true, 𝑃𝑃(6): false,…

𝑃𝑃(43): true, 7 x 5-cents-stamp + 1 x 8-cents-stamp

𝑃𝑃(44): true, 4 x 5-cents-stamp + 3 x 8-cents-stamp

3 x 5-cents-stamp (15 cents) is replaced by 2 x 8-cent-stamp (16 cents)

𝑃𝑃(45): true, 9 x 5-cents-stamp

3 x 8-cents-stamp (24 cents) is replaced by 5 x 5-cent-stamp (25 cents)

Condition: have at least 3 x 5-cents-stamp or 3 x 8-cents-stamp

𝑃𝑃(𝑛𝑛): true for 𝑛𝑛 ≥ 28

Formalizing Proofs

When you are asked to prove a statement by mathematical induction, you should first think about why the
statement is true, using inductive reasoning. Explain why induction is the right thing to do, and roughly why the
inductive case will work.

𝑎𝑎𝑛𝑛 − 𝑏𝑏 𝑛𝑛 = (𝑎𝑎 − 𝑏𝑏)(𝑎𝑎𝑛𝑛−1 + ⋯ . )


Strong Induction

4. For each of the statements below, give a domain of discourse for which the statement is true, and a domain for
which the statement is false.

(a) ∀x∃y(y =x2).

Domain for the case the statement is true.

Domain: ℕ, i.e., 𝑥𝑥, 𝑦𝑦 ∈ {0,1,2,3, … }

Domain for the case the statement is false.

Domain: 𝑥𝑥, 𝑦𝑦 ∈ {… , −3, −2, −1}

if x=-2, y=4 does not belong to the given domain.


(b) ∀x∀y(x1y→∃z(x-y=z)).

Domain for the case the statement is false.

Domain: 𝑥𝑥, 𝑦𝑦, 𝑧𝑧 ∈ {… , −3, −2, −1}


x=-2, y=-4, z=-2-(-4)=2 does not belong to the given domain.

You might also like